Households’ Willingness-to-Pay for Value Addition in Azadirachta indica (Neem) Based Products in Ibadan Metropolis (2021)
Azadirachta indica popularly referred to as Neem plant is one of the plants found in almost all parts of the world. In Nigeria, the plant is famously consumed in its raw form, but efforts have been made to present the products in a variety of forms through processing. Despite this value addition, however, little research has been done in assessing the readiness of the consumers to pay more for the extra entrepreneurial labour in presenting the product in a more acceptable way. Thus, this study investigates household’s willingness-to-pay (WTP) for value addition in Neem-based products in Ibadan, Oyo State, Nigeria. Primary data were collected from one hundred and twenty-one (121) respondents using multi-stage sampling procedure. Data were analysed using descriptive statistics, contingent valuation method and logit regression model. Results show that 57.85% of the respondents were willing to pay highest amount for NAFDAC certification (𝑋 ̅: N615.57±116.48) followed by Brand name (53.72%; 𝑋 ̅: N538.92±328.26). Respondents were also mostly familiar with Neem powder (58.67%) and Neem soap (53.71%). However, this did not translate to usage. Age, gender, education level, occupation type and monthly expenditure were some of the factors determining WTP. The study recommends creating adequate awareness on the benefits of Neem-based products as well as formulation of policies that guarantee safety of product consumption.